An Empirical Analysis of Unsolicited Commercial E-mail. Issue 1 (June 2014) - Kumar, Satinder; Sharma, Rishi Raj
The online consumer marketplace is growing at an exponential rate. At the same time, technology has enhanced the capacity of online companies to promote products unethically. To ensure consumer confidence in this new marketplace and its continued growth, consumer concerns about spamming must be addressed. In the present study, the factor analysis technique was applied on the responses of respondents with regard to variables related to the issue of spamming in e-marketing, and four factors were extracted. The extracted factors were: Commercial spam, e-mail marketing threat, regulating spam and violation of privacy. The structural equationing model (SEM) has been used to confirm the factors' results. The results indicated that the respondents were negatively inclined towards e-mail marketing. Respondents felt that the marketers are unethical, using e-mail as the promotion of marketing tool.